John Steinbeck hunting in Poland - Piotr Baracz:::Creator::::::::::::
John Scanlan of the Department of State based in Poland, John Steinbeck, Boris Tomashevski, a Soviet Formal literary theorist, on a boar hunt in the Kraina Tysiaca Jezior region in Poland. John Steinbeck is quoted saying about the hunt: 'They were running so nicely I didn't have the heart to take aim.' See also photos 0-957; 0-355; 1-325; 1-344; 1-496; 1-497. Original is in the safe.